The C677t and A1298c Polymorphisms of Methylenetetrahydrofolate Reductase (Mthfr) Gene (Annals of Medical Research, 2021)
Aim: Methylenetetrahydrofolate reductase is an important enzyme of folate metabolism. Human MTHFR gene is localized to chromosome 1p36.3 and coded MTHFR enzyme which consists of 563 amino acids. Some mutations seen in the MTHFR gene, resulting in the inactivation of the enzyme, cause hyperhomocysteinemia and homocystinuria as being important risk factors for cardiovascular and cerebrovascular diseases. According to the numerous literature data, polymorphic variant of the MTHFR-encoding gene, is associated with hyperhomocysteinemia, vascular pathologies, neural tube defects, dementia, perinatal mortality, mental disorders, neurodegenerative disorders, cancer and migraine. The aim of this study was to determine allelic frequencies of the polymorphic MTHFR gene C677T, A1298C. In this regard, we have investigated the allelic frequencies of C677T and A1298C polymorphisms of the MTHFR gene in 222 (109 females and 113 males) randomized individuals around Sivas.
Keywords: Methylenetetrahydrofolate Reductase, Polimorphism, Homocysteine